Persepsi Konsumen Sayuran di Kota Manado terhadap Produk Sayuran Bebas Pestisida - Christy O. Pua; Jen Tatuh; Vicky R.B. Moniaga; Leonardus R. Rengkung (COCOS, 2014)
ABSTRACTChristy O. Pua.The Perception of Vegetable’s Consumers in Manado City about Free Pesticide Vegetables Product. Under guidance of Jen Tatuh as chairman, and Vicky R. B. Moniaga and Leonardus R. Rengkung as members.The objective of this research is to measure the consumer’sperception in Manado City to some aspects about free pesticide vegetables product, especially about secure aspect for consumer’s health. The method used in this research is survey method. This research uses primary data. Sampling method used in this research is accidental sampling. The primary data are obtained from respondents, who buy vegetable in Pinasungkulan Traditional Market and Hypermart Supermarket, total respondents are 40. Data is analysed by descriptive used Likert Scale.The result shows that perception of vegetable consumer about free pesticide vegetable product classified as strong. It means that they have high awareness about the those products. The highest of indicator perception index is the consumer persception about savibility product for healthness, it means people have already know that free pesticide vegetable is healthy. The indicator lowest perception index is the consumen persception that the habit of consumption the free pesticide vegetable is as a tradition in the family, it means that consumer is used to consumed free pesticide vegetable. The reasons for consumer buying free pesticide vegetable product are the prices relatively expensive compared with non free pesticide vegetable product, and it is hard to find that product’s in market, which makes the consumers, still doubt to consume of free pesticide vegetable products as a lifestyle or a tradition in the family, especially consumer who buy vegetables in traditional market.